A Shared Prebiotic Formation of Neopterins and Guanine Nucleosides from Pyrimidine Bases. Issue 39 (24th June 2022) - Menor‐Salván, César; Burcar, Bradley T.; Bouza, Marcos; Fialho, David M.; Fernández, Facundo M.; Hud, Nicholas V.
Abstract: Invited for the cover of this issue are the groups of César Menor‐Salván, Facundo Fernández and Nicholas V. Hud at the University of Alcala and the Georgia Institute of Technology. The image depicts the authors contemplating the origin of pterins and guanosine nucleosides from a common precursor, with the art‐gallery setting embodying their feeling that the common synthetic pathways of these molecules in both the prebiotic world and in biochemistry is a natural work of (chemical) art. Read the full text of the article at 10.1002/chem.202200714 . Abstract : " Our results provide the first glimpse of a possible common origin of purine nucleosides and pterins, thus suggesting a very deep, common history of enzyme cofactor and RNA synthesis ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202200714 ).